TEKNIK-TEKNIK BARU PADA POLA PRODUKSI UNTUK MEMPERCEPAT PRODUKSI GAS PADA FORMASI COAL BED METHANE (CBM) YANG TEBAL MELALUI PENGGUNAAN SACRIFICE WELL - J S Purba, Rafael
Coal Bed Methane (CBM) is one of the unconventional resource that has potentialy promising, especially in Indonesia. Gas reserves of CBM's own resources estimated at 450 TSCF in Indonesia and make this country is in the 6th position of countries with the largest CBM resources in the world. However, regulatory and technical limitations slow the progression of the exploitation of these resources. One of the fundamental technical problem is related to the length of the gas production that can occur as a result of the length of the dewatering time. Many studies have been developed related to the production of CBM, and this paper discusses the several characteristics, patterns and techniques regarding the production of methane gas from coal through the use of sacrifice well. This paper specifically discusses the characteristics and patterns of production which correspond in producing methane from coal which has a thick reservoir as well as the Indonesian CBM reservoir is relatively thick. Characteristics and patterns and techniques of production itself derived through analysis and evaluation of several scenarios that have been run through the simulator. And the results showed that the production of the thick CBM reservoir with some sensitivity patterns of production through the use of sacrifice well have an influence on the production of gas, and water on the exploitation of CBM resources. In other words, through the use of new techniques that are discussed in this paper have an impact on reducing the dewatering time and effectively implemented in Indonesia, which has a thick CBM formations.